Editorial CIRF — on phenomenology and its surroundings - Bello, Angela Ales; Menin, Ademir (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2021)
With this issue, Aoristo – International Journal of Phenomenology, Hermeneutics and Metaphysics (a vehicle created during the period of unequivocal development of phenomenology studies at the Universidade Estadual do Oeste do Paraná – UNIOESTE, recognized in 2013) reaffirms its vocation as a disseminator of phenomenological knowledge, especially that of German origin, in Brazil and in international extensions.